Linear Analysis of the Static and Dynamic Responses of the Underwater Axially Moving Cables to Bucket Loads - Daiki Itoh; Yoshiki Nishi (Journal of Marine Science and Engineering, 2019)
In this study, the mechanics of an axially moving cable that is used to acquire mineral resources from the seafloor are theoretically and numerically investigated by focusing on the extent to which a load of buckets affects the cable deflection. In particular, we construct the theoretical model of a cable, and its solutions are numerically determined using the mode expansion method. The results of the simulations performed using a varying number of buckets show that the cable deflects in response to the passage of each bucket. As the total number of buckets increases, the load of buckets acts as a continuous load. An increase in the total number of buckets naturally leads to an increase in the total load on the cable, resulting in the deviation of the paths of the buckets from a path under the zero-load state. These properties should be considered while designing cables.